Penyelesaian Sengketa Tanah Pekarangan Desa di Desa Adat Sulahan Kecamatan Susut Kabupaten Bangli - I Putu Ade Surya; I Made Suwitra; I Ketut Sukadana (Jurnal Interpretasi Hukum, 2020)
Land in human life has a very important role because it is a source of welfare, prosperity and life. In addition, land has a close relationship with humans because land has economic value for human life and can produce natural resources for many people. There are 2 (two) rights to land in customary law, namely the right to land controlled by individuals and the right to land controlled by customary law communities or customary land. Based on this, the formulation of the problem can be taken as follows: (1) How is the existence of the village yard land in the awig-awig of Sulahan Traditional Village, Susut District, Bangli Regency? (2) How is the settlement of a village yard land dispute case in the Sulahan Traditional Village, Susut District, Bangli Regency? The research method used is empirical legal research, namely legal research which functions to see the law in a real sense and to examine how the law works in society. The approach to the problem used is in the form of a sociology of law approach, which is a legal research that examines legal facts that exist in society. The results showed that the settlement of village yard land disputes in the Sulahan Traditional Village was usually resolved by kinship with Bendesa Adat acting as the mediator. Mediation carried out by Prajuru of Sulahan Traditional Village in resolving village yard land disputes that occurred in Sulahan Traditional Village was carried out at Pura Desa Sulahan. The purpose of the mediation was carried out at the Sulahan Village Temple because of its strategic location. Before conducting mediation, the Prajuru Desa Adat and the disputing parties will hold a prayer first so that the mediation can run smoothly so that there are no disputes.